2017
DOI: 10.1111/1468-2427.12455
|View full text |Cite
|
Sign up to set email alerts
|

Family or Money? The False Dilemma in Property Dispossession in Shanghai

Abstract: This article examines the lived experiences of property dispossession caused by the World Expo 2010 in Shanghai. Specifically, it examines the category of the family, which is overlooked in the existing literature, and probes into the political production of family conflicts and breakdowns. It characterizes the prevailing regime of dispossession in contemporary China as decentralized legal authoritarianism and argues that the organization of the Expo‐induced dispossession deviated from this because of the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
2
12
0
1
Order By: Relevance
“…The holdout households were taken to court by the village shareholding company and compulsorily evicted. These developments support observations of how the deployment of market means and economic inducements may serve to individualize and fragment rural society during redevelopment processes, and undermine the social basis for collective action (Chuang, ; Levien, ; Zhang, ).…”
Section: Class Relations and Collective Action In Urbanized Villagessupporting
confidence: 71%
See 1 more Smart Citation
“…The holdout households were taken to court by the village shareholding company and compulsorily evicted. These developments support observations of how the deployment of market means and economic inducements may serve to individualize and fragment rural society during redevelopment processes, and undermine the social basis for collective action (Chuang, ; Levien, ; Zhang, ).…”
Section: Class Relations and Collective Action In Urbanized Villagessupporting
confidence: 71%
“…Drawing on the notion of ‘value grabbing’ (Andreucci et al ., ), it is shown that the unequal distribution of value appropriated from land amongst the classes of actors involved in land development provides the basis for a new kind of contentious politics. In theorizing the new mechanisms by which accumulation by dispossession is unfolding on the fringes of Chinese cities, this article seeks both to deepen understandings of land politics and accumulation strategies in contemporary China and to contribute to the literature on urbanization and dispossession in the global South (Levien, ; Gillespie, ; Shin, ; Mbiba, ; Zhang, ).…”
Section: Introductionmentioning
confidence: 99%
“…The relocation of millions of residents and forced evictions have been highlighted by many studies as major social problems of China’s mega developments (Hsing ; Jiang et al ; Shin ; Zhang , ). However, through the case of Neighbourhood No.57, we find that the biggest social problem in Lingang is in‐situ marginalisation whereby residents, who have not been relocated, suffer from declining public services and environmental quality due to nearby industrial activities.…”
Section: Resultsmentioning
confidence: 99%
“…However, increasingly more studies express doubt that the concept of neoliberalisation is suited to explain the Chinese urban development process (Wu ; Wu and Phelps ). In China, large‐scale displacement and forced evictions from mega developments such as the Shanghai Expo or the Beijing 2008 Olympic games continue to be of great concern (Shin ; Zhang ). Land expropriation has displaced millions of residents in order to make space for new developments (Shin ; Wu et al ).…”
Section: The Social Impact Of Mega Urban Projectsmentioning
confidence: 99%
“…As a key vehicle for spatialized capital accumulation, urban redevelopment in pursuit of short-term profit has led to widespread and relentless displacement, forced demolition and social-spatial marginalization in Chinese cities (He, 2012; He and Lin, 2015; Zhang, 2017). This led to a rise in social conflict and resistance in the late 2000s, threatening the legitimacy of the ruling party.…”
Section: A Crisis Of Crisis Management? the Socio-economic Implicatiomentioning
confidence: 99%